Análise de eficiência energética de instalação fotovoltaica integrada a edifício (BIPV) com painéis fotovoltaicos orgânicos (OPV) em fachadas verticais - Luiza de Queiroz Corrêa (2023)
Building-integrated photovoltaics play a key role in the reduction of greenhouse gases emission towards sustainability in the building and construction sector. The organic solar technology holds several advantages such as lightweight, flexibility and semitransparency, suiting well for this type of application. Integrated to windows and facades, they offer a dual-benefit: at one hand offers a barrier to part of the solar radiation, adding thermal comfort to the indoor environment, while at the other generates off-grid power. Besides that, organic devices are known to be more efficient than traditional photovoltaics based in silicon in diffuse and low light conditions. Nevertheless, only few studies had been conducted in the area employing large-area commercial modules, in real operational conditions for a long-term period. This work has the purpose to reduce this gap and shine a light on this debate bringing an analysis based on real data of a set of organic panels laminated in glass in a vertical installation. For this, several linear regression models were tested to predict the energy generation from meteorological data and solar position throughout four years of operation, and the best models developed achieved 0.76 and 0.81 values for R² with validation data, respectively for simple and multiple regressions.